MAYBE Initial complexity problem: 1: T: (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] (?, 1) f2(a, b, c) -> f300(a, b, d) [ a = b ] (1, 1) f1(a, b, c) -> f2(a, b, c) start location: f1 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] (1, 1) f1(a, b, c) -> f2(a, b, c) start location: f1 leaf cost: 1 A polynomial rank function with Pol(f2) = -3*V_1 + 3*V_2 - 2 Pol(f1) = -3*V_1 + 3*V_2 - 2 orients all transitions weakly and the transition f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] strictly and produces the following problem: 3: T: (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] (1, 1) f1(a, b, c) -> f2(a, b, c) start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a, b, c) with all transitions in problem 3, the following new transitions are obtained: f1(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] We thus obtain the following problem: 4: T: (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] with all transitions in problem 4, the following new transition is obtained: f1(a, b, c) -> f2(a + 2, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b ] We thus obtain the following problem: 5: T: (1, 3) f1(a, b, c) -> f2(a + 2, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 2, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b ] with all transitions in problem 5, the following new transition is obtained: f1(a, b, c) -> f2(a + 3, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b ] We thus obtain the following problem: 6: T: (1, 4) f1(a, b, c) -> f2(a + 3, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 3, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b ] with all transitions in problem 6, the following new transition is obtained: f1(a, b, c) -> f2(a + 4, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b ] We thus obtain the following problem: 7: T: (1, 5) f1(a, b, c) -> f2(a + 4, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 4, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b ] with all transitions in problem 7, the following new transition is obtained: f1(a, b, c) -> f2(a + 5, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b ] We thus obtain the following problem: 8: T: (1, 6) f1(a, b, c) -> f2(a + 5, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 5, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b ] with all transitions in problem 8, the following new transition is obtained: f1(a, b, c) -> f2(a + 6, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b ] We thus obtain the following problem: 9: T: (1, 7) f1(a, b, c) -> f2(a + 6, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 6, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b ] with all transitions in problem 9, the following new transition is obtained: f1(a, b, c) -> f2(a + 7, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b ] We thus obtain the following problem: 10: T: (1, 8) f1(a, b, c) -> f2(a + 7, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 7, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b ] with all transitions in problem 10, the following new transition is obtained: f1(a, b, c) -> f2(a + 8, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b ] We thus obtain the following problem: 11: T: (1, 9) f1(a, b, c) -> f2(a + 8, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 8, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b ] with all transitions in problem 11, the following new transition is obtained: f1(a, b, c) -> f2(a + 9, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b ] We thus obtain the following problem: 12: T: (1, 10) f1(a, b, c) -> f2(a + 9, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 9, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b ] with all transitions in problem 12, the following new transition is obtained: f1(a, b, c) -> f2(a + 10, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b ] We thus obtain the following problem: 13: T: (1, 11) f1(a, b, c) -> f2(a + 10, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 10, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b ] with all transitions in problem 13, the following new transition is obtained: f1(a, b, c) -> f2(a + 11, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b ] We thus obtain the following problem: 14: T: (1, 12) f1(a, b, c) -> f2(a + 11, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 11, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b ] with all transitions in problem 14, the following new transition is obtained: f1(a, b, c) -> f2(a + 12, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b /\ a + 11 >= b + 1 /\ a + 11 >= b ] We thus obtain the following problem: 15: T: (1, 13) f1(a, b, c) -> f2(a + 12, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b /\ a + 11 >= b + 1 /\ a + 11 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 12, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b /\ a + 11 >= b + 1 /\ a + 11 >= b ] with all transitions in problem 15, the following new transition is obtained: f1(a, b, c) -> f2(a + 13, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b /\ a + 11 >= b + 1 /\ a + 11 >= b /\ a + 12 >= b + 1 /\ a + 12 >= b ] We thus obtain the following problem: 16: T: (1, 14) f1(a, b, c) -> f2(a + 13, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b /\ a + 11 >= b + 1 /\ a + 11 >= b /\ a + 12 >= b + 1 /\ a + 12 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 13, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b /\ a + 11 >= b + 1 /\ a + 11 >= b /\ a + 12 >= b + 1 /\ a + 12 >= b ] with all transitions in problem 16, the following new transition is obtained: f1(a, b, c) -> f2(a + 14, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b /\ a + 11 >= b + 1 /\ a + 11 >= b /\ a + 12 >= b + 1 /\ a + 12 >= b /\ a + 13 >= b + 1 /\ a + 13 >= b ] We thus obtain the following problem: 17: T: (1, 15) f1(a, b, c) -> f2(a + 14, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b /\ a + 11 >= b + 1 /\ a + 11 >= b /\ a + 12 >= b + 1 /\ a + 12 >= b /\ a + 13 >= b + 1 /\ a + 13 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c) -> f2(a + 14, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b /\ a + 11 >= b + 1 /\ a + 11 >= b /\ a + 12 >= b + 1 /\ a + 12 >= b /\ a + 13 >= b + 1 /\ a + 13 >= b ] with all transitions in problem 17, the following new transition is obtained: f1(a, b, c) -> f2(a + 15, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b /\ a + 11 >= b + 1 /\ a + 11 >= b /\ a + 12 >= b + 1 /\ a + 12 >= b /\ a + 13 >= b + 1 /\ a + 13 >= b /\ a + 14 >= b + 1 /\ a + 14 >= b ] We thus obtain the following problem: 18: T: (1, 16) f1(a, b, c) -> f2(a + 15, b, c) [ a >= b + 1 /\ a >= b /\ a + 1 >= b + 1 /\ a + 1 >= b /\ a + 2 >= b + 1 /\ a + 2 >= b /\ a + 3 >= b + 1 /\ a + 3 >= b /\ a + 4 >= b + 1 /\ a + 4 >= b /\ a + 5 >= b + 1 /\ a + 5 >= b /\ a + 6 >= b + 1 /\ a + 6 >= b /\ a + 7 >= b + 1 /\ a + 7 >= b /\ a + 8 >= b + 1 /\ a + 8 >= b /\ a + 9 >= b + 1 /\ a + 9 >= b /\ a + 10 >= b + 1 /\ a + 10 >= b /\ a + 11 >= b + 1 /\ a + 11 >= b /\ a + 12 >= b + 1 /\ a + 12 >= b /\ a + 13 >= b + 1 /\ a + 13 >= b /\ a + 14 >= b + 1 /\ a + 14 >= b ] (1, 2) f1(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (3*a + 3*b + 2, 1) f2(a, b, c) -> f2(a + 1, b, c) [ b >= a + 1 ] (?, 1) f2(a, b, c) -> f2(a + 1, b, c) [ a >= b + 1 /\ a >= b ] start location: f1 leaf cost: 1 Complexity upper bound ? Time: 1.262 sec (SMT: 1.163 sec)